Linking strategic flexibility and operational efficiency: The mediating role of ambidextrous operational capabilities - Kortmann, Sebastian; Gelhard, Carsten; Zimmermann, Carsten; Piller, Frank T. (Journal of Operations Management, 2014)
AbstractWe elucidate the important, though complex, relationship between strategic flexibility and operational efficiency. We incorporate insights from the dynamic resource‐based view, ambidexterity literature and managerial practice to explain how two ambidextrous operational capabilities, i.e., mass customization capability and innovative ambidexterity, fully mediate the relationship between strategic flexibility and operational efficiency. Using top‐level executive data in India and the United States of America, our structural equation models show that ambidextrous operational capabilities link strategic flexibility and operational efficiency. While informing the debate on developing sustainable competitive advantage, we derive important theoretical and managerial implications for both operations management and strategic management.